Application of Financial Accountability in the Village of Polohungo - Agustin Polinto; Ikram Muhammad; Sukrianto (Journal of Economic, Business, and Administration (JEBA), 2021)
This study has a problem formulation, namely how to implement financial accountability in the village of Polohungo and has the aim of describing the application of village financial accountability in Pulohungo Village. This research uses descriptive research with a qualitative method approach, descriptive research type. This research uses data analysis techniques of the Miles and Huberman model with the following stages 1) Data Reduction, 2) Data Display and Conclusion Chart Drawing/Verification. The results of this study indicate that the application of the Pulohungo Village Financial Accountability is satisfactory, and in accordance with the prevailing laws and regulations. In ADD and DD planning, Planning and Development Deliberation activities have been carried out both at the hamlet level, at the village level, and at the sub-district level by involving BPD, LPMD, and representatives from the community. The purpose of this activity is to accommodate the aspirations of all elements, both the community and the village administration so that it is hoped that village development will take place as planned and in accordance with the priority scale. Implementation accountability has taken place satisfactorily and in accordance with established procedures. The use of ADD and DD funds have been used in accordance with the ADD Fund Usage Plan.